Du voyageur à la reporter, des proximités variables - Charlotte Biron (Contextes)
Comparing Arthur Buies’s travel in California and Gabrielle Roy's articles on western Canada, this paper explores the different purposes of intimacy in travel writing published in newspapers and in the genre of reportage, two genres historically linked. Travelers and journalists such as Buies or Roy use an autobiographical « I » establishing a sense of intimacy in counterpoint with the travel contingencies, the outside and the various encounters with strangers. With the rise of news and mass media, however, the reporter develops a different relationship with his subject from the ones the traveler had. In her articles, Roy tries to bring the reader closer to the people she meets and describes, whereas Buies rather isolates himself throughout his journey remaining as close as possible to his reader. Their comparison reveals the reconfiguration of the relationship between the journalist, the readership and alterity at the turn of the century.